The value of percutaneous transhepatic treatment of biliary strictures following pediatric liver transplantation - Cardarelli-Leite, Leandro (Radiol Bras, 2017)
OBJECTIVE: To evaluate the percutaneous transhepatic approach to the treatment of biliary strictures in pediatric patients undergoing liver transplantation. MATERIALS AND METHODS: This was a retrospective study of data obtained from the medical records, laboratory reports, and imaging examination reports of pediatric liver transplant recipients who underwent percutaneous transhepatic cholangiography, because of clinical suspicion of biliary strictures, between 1st September 2012 and 31 May 2015. Data were collected for 12 patients, 7 of whom were found to have biliary strictures. RESULTS: In the 7 patients with biliary strictures, a total of 21 procedures were carried out: 2 patients (28.6%) underwent the procedure twice; 3 (42.8%) underwent the procedure three times; and 2 (28.6%) underwent the procedure four times. Therefore, the mean number of procedures per patient was 3 (range, 2–4), and the average interval between them was 2.9 months (range, 0.8–9.1 months). The drainage tube remained in place for a mean of 5.8 months (range, 3.1–12.6 months). One patient presented with a major complication, hemobilia, which was treated with endovascular embolization. Clinical success was achieved in all 7 patients, and the mean follow-up after drain removal was 15.4 months (range, 5.3–26.7 months). CONCLUSION: The percutaneous transhepatic approach to treating biliary strictures in pediatric liver transplant recipients proved safe, with high rates of technical and clinical success, as well as a low rate of complications.